Existential Humanistic Realization: Case Study in Urban and Rural Elementary School, Yogyakarta - Sugeng Riyanto, Andayani, Muhammad Rohmadi, Sumarlam (International Journal of Advanced Science and Technology, 2020)
The interaction of elementary school students is more with gadgets or social media, the playing environment while at home, and the role of TV that provides programs verbally violence requires ongoing assistance by teachers and parents. The existence of elementary schools, which are located in villages (rural) and urban (urban) will affect their behavior. The role of the teacher in done through humanistic extension is support to confidence, explore the potential, and invite students to evaluate an error in behavior. Porpose of writing, Identify humanistic existential realization in urban and rural elementary schools in Yogyakarta. Research Background is about the realization of humanistic extension: a case study of Yogyakarta urban and rural elementary schools, namely Muhammadiyah Pakel Elementary school and MI Maarif. This research uses a qualitative approach and data sources in this study were taken from interviews with class teachers as those who apply existential humanistic, elementary school students, and school principals. In addition, the results of the audio-visual documentation is photos, videotapes, recordings, etc. Data sources were taken from observations result and field notes during the research process. Research Finding Humanistic existential realization in Elementary School of Muhammadiyah Pakel is held in the classroom, headmaster rooms, and student’s house. The classroom implementation is done through interaction directly such teacher assistance in learning and teaching activity. MI Maarif applied humanistic existential with some preventives. First, put school rule in every classroom so students can remind prohibition and notice. Second, patch reward board as inducement for students. When students obey the rule he or she will give a star that is prepared by teachers and until now this activity is effective. Third, teacher role is to assistance even inside and outside of classroom.